Desensitization of a Case with Generalized Anxiety - Bharathraj J (Journal of All India Institute of Speech and Hearing, 1970)
Here follows an illustration of  the Systematic Desensitization treatment of a case with Generalized Anxiety symptoms of three  years duration. Systematic desensitization with hierarchies in selected areas decreased anxiety very considerably  after 36 sessions of treatment.  Pre and Post-therapy assessment on  Medico-Psychological Questionnaire revealed a significant change in the profile. Therapeutic gains were retained even after two years of therapy.